LIFE CYCLE ASSESSMENT OF POINT-OF-LAY BIRDS TO FROZEN CHICKEN PRODUCTION IN A TROPICAL ENVIRONMENT - TEMITAYO A. EWEMOJE; OLUFEMI P. ABIMBOLA; OLAYINKA A. OMOTOSHO (Journal of Engineering Studies and Research)
The study examined four scenarios for reduction of environmental impacts with use of 100 % purchased electricity in all processing activities as first scenario while second scenario was the use of 100 % electricity from diesel generators. Third and fourth scenarios were to use 50 % each of both purchased electricity and diesel-generated electricity in all activities. Most of the Energy Use (EU) came during the freezing process. Global Warming Potential (GWP) value for Scenario 2 is predominantly higher than the values for other three scenarios. The results show that the major source for global warming potential for Scenario 2 is the freezing process, whereas for the other three scenarios the animal management represents the main contributor. Similar to GWP, the Acidification Potential and Eutrophication Potential values for Scenario 2 were higher, although very small and this may be attributed to diesel generators emitting slightly higher amounts of NOx and SOx.